Analysis of Factors Affecting the Poverty Gap Index in Aceh Province 2017-2019 - Rizky Mahesa Wahid; Sudati Nur Sarfiah (Research Horizon, 2021)
The poverty gap index in Aceh Province during the 2017-2019 period tends to decrease. This study aims to determine the appropriate modelling in finding the factors that affect the poverty gap index in Aceh Province. The data used is secondary data obtained from the Central Statistics Agency for Aceh Province from 2017-2019. The dependent variable used is the poverty gap index (P1). Meanwhile, the independent variables are the open unemployment rate, crime rate, dependency ratio and sex ratio. The best model obtained is the Fixed Effect Model (FEM). The factors that influence the poverty gap index are the dependency ratio, while the open unemployment rate, crime rate and sex ratio do not affect the poverty gap index.